Pengendalian Inflasi Dalam Penilaian Ekonomi Makro Islam Di Indonesia - Ananta Delyana Mafikah; Silvi Indah Nurvita Sari; Ahmad Izul Arif Zairifli; Eny Latifah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Inflation control is a very important aspect in macroeconomic assessments, including from an Islamic economic perspective. The main focus of this research examines the mechanisms and principles of controlling inflation within an Islamic macroeconomic framework, with a focus on monetary and fiscal policies that are in accordance with sharia. This approach emphasizes economic justice, fair distribution of wealth, and balance between supply and demand in the market. Instruments such as the prohibition of usury and the use of commodity-based currencies are discussed as potential tools to maintain price stability. Apart from that, this research also evaluates the role of Islamic financial institutions in promoting economic stability and reducing the rate of inflation. The research results show that the application of Islamic economic principles can provide an effective alternative solution to control inflation, while maintaining justice and the welfare of society as a whole. Through this analysis, it is hoped that it can contribute to the development of better and more sustainable economic policies in an Islamic context.